Sosialisasi Alur Pelayanan Administrasi Kependudukan Kelurahan Merdeka Dalam Kegiatan Praktik Kerja Lapangan di Lingkungan Kelurahan Merdeka - Jordan Joel Hiroshi Pinem; Malida Putri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem of residents with awareness of the flow of sub-district administrative services is a problem related to the lack of information, education and outreach from the sub-district to the community about how to process population documents. mezzo intervention method (intervention with groups and communities), macro (intervention through policy and social action). Group work, namely to facilitate individual development both intellectually, emotionally and socially through group activities. Socialization of the Merdeka Village Population Administration Service Flow is a form of Field Work Practice mini project.